Cultural heritage of the Qin-Shu Ancient Road in Shaanxi: Spatial distribution characteristics and influencing factors - Kankan Li; Ziqiang Huang; Yinghui Pang; Sijie Chen; Yijing Fan; Menglei Yin; Chengyong Shi (PLoS ONE, 2025)
This study investigates the spatial and temporal distribution and the influencing factors of 579 cultural heritage sites along the Qin–Shu Ancient Road in Shaanxi Province, employing kernel density estimation, buffer analysis, and geographic detectors. Three key findings emerge: (1) The spatial pattern is characterized by a “line-belt-core” structure, with a belt-like aggregation along the Xi’an-Baoji-Hanzhong axis. Core concentrations are found in Xi’an (181 sites), Hanzhong (159 sites), and Ankang (122 sites), with secondary concentrations in Baoji (72 sites) and Shangluo (36 sites). The spatial distribution of heritage types—such as ancient road relics, traditional villages, historic architecture, cave temples and rock carvings, modern historic sites, and tomb complexes—is influenced by topography and human factors. (2) The spatiotemporal evolution occurs in three stages: “natural selection,” “technological breakthrough,” and “cultural adaptation.” It begins with linear valley distributions during the Prehistoric-Qin-Han period, expands through mountainous regions with plank-road engineering in the Wei-Jin-Sui-Tang period, and shifts towards settlements and tomb complexes from the Song to Qing dynasties, marking a transition from transport corridors to integrated cultural landscapes. (3) Natural factors—such as elevation, precipitation, slope, aspect, and proximity to hydrological networks—are the primary drivers, while anthropogenic factors, including ancient route alignment and regional GDP, have a secondary influence. Significant interactions were observed between elevation and aspect, elevation and precipitation, and between hydrological proximity, aspect, and precipitation. These findings offer both theoretical insights and practical guidance for heritage conservation planning and the development of regional cultural tourism along the Qin-Shu Ancient Road.